Ã´â¬Â°Â¸Ã´ÂÂ©Â¥Ã´ÂÂâºÃ´âÂ©Â¦Ã´â¬Â¡Å¸Ã´â¬Â Â¾Ã´â¬Â¡â¦Ã´â¬Â¡Â¿Ã´â¬Â¼Â Ã´â¬Â´Â¾Ã´ÂÂ¼Â²Ã´â¬Â¡Â¢Ã´ÆÂÂ Ã´âÂÂ (COLLABORATIVE WRITING IN TEACHING SAKUBUN) - Prasetiani, Dyah (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2011)
This study was intended to find out how collaborative writing gives better effects to thestudentÃ¢â¬â¢s Japanese ability in writing. There were three aspects that investigated: (1) Teachinglearning process, (2) Learner and teacher finding problems in collaborative writing, (3)StudentÃ¢â¬â¢s suggestion of collaborative writing. This study employed descriptive qualitativedesign by using classroom observations and interview method to collect the data. The majorfindings of this study are: (1) Collaborative writing enable student to practice and developwriting skills, however, the lack of grammar ability cause peer correction not appropriate, (2)Teaching learning sakubun becomes more various by using this technique.